1990
DOI: 10.2135/cropsci1990.0011183x003000050003x
|View full text |Cite
|
Sign up to set email alerts
|

Prodiamine Effects on Quality and Rooting of Kentucky Bluegrass Turf

Abstract: As new herbicides are investigated for use on turf, it is important to study the effects continued use of these materials have on desirable grass species. A field investigation was conducted to determine the influence of prodiamine [2,4‐dinitro‐N3,N3‐dipropyl‐6‐(trifluoromethyl)‐1.3‐benzenediamine] application rate and frequency on Kentucky bluegrass (Poa pratensis L.) turf over a 4‐yr period. Root mass and turfgrass density decreased following prodiamine treatment. Turfgrass quality ratings decreased as prodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…A recent literature search revealed no other reports of preemergent herbicide safety on ornamental grasses. Possibly herbicides, such as pendimethalin (Herrick and Ilnicki, 1985), benefin (Jagschitz, 1985), benefin plus trifluralin (Sawyer and Jagschitz, 1987), isoxaben (Colbert and Ford, 1987), MON 15100 (Parrish et al, 1988), prodiamine (Hummel et al, 1990), and oxadiazon (Sawyer and Jagschitz, 1987), that are safe on turfgrasses might also be safe on ornamental landscape grasses. However, these products have not been tested for safety on ornamental landscape grasses.…”
mentioning
confidence: 99%
“…A recent literature search revealed no other reports of preemergent herbicide safety on ornamental grasses. Possibly herbicides, such as pendimethalin (Herrick and Ilnicki, 1985), benefin (Jagschitz, 1985), benefin plus trifluralin (Sawyer and Jagschitz, 1987), isoxaben (Colbert and Ford, 1987), MON 15100 (Parrish et al, 1988), prodiamine (Hummel et al, 1990), and oxadiazon (Sawyer and Jagschitz, 1987), that are safe on turfgrasses might also be safe on ornamental landscape grasses. However, these products have not been tested for safety on ornamental landscape grasses.…”
mentioning
confidence: 99%
“…Demoeden et al (5) reported that prodiamine 65 WDG at 0.56, 1.12, or 2.24 kg ai/ha and pendimethalin 1.7G at 3.36 kg ai/ha significantly reduced root production of a mature stand of perennial ryegrass (Lolium perenne L.) on a golf course fairway and enhanced leaf spot injury. Hummel et al (9) reported rooting, stand density, and quality of Kentucky bluegrass turf decreased with increas ing application rate and frequency of prodiamine. Root mass was 73% of the untreated on annually treated plots compared with 51 % on biennially treated plots receiving a 4.5 kg ai/ha rate of prodiamine.…”
Section: Introductionmentioning
confidence: 99%
“…Sybouts (9) reported that prodiamine provides good lReceived for publication Oct. 6,1993 long-term control of annual grass weeds in established turf. Prodiamine at 0.56 and 1.12 kglha controlled large crabgrass 93 and 95% respectively at 27 wk after spring applications.…”
Section: Introductionmentioning
confidence: 99%